PERSEPSI MASYARAKAT TENTANG AYAM BULEK DALAM PERKAWINAN DI NAGARI TAPAN KECAMATAN BASA AMPEK BALAI TAPAN KABUPATEN PESISIR SELATAN - Sofila, Dika; Arifin, Zainal; Firdaus, Firdaus (Pendidikan Sosiologi, 2014)
The society in Tapanused of ayam bulek tradition in process of marriage. Reception ayam bulek is usually to do after they are promise each other or the woman marriage come to manâs house. Ayam bulek is response from manâs family side because manâs family give an expensive thing (gold) to the womanâs family side, if the tradition ayam bulek not done by man side, so the manâs family sides will get of bashful to the society. The purpose of research is want to know the society perception about ayam bulek traditionÂ in mariage by Nagari Tapan. The research is used fenomonology teory by Alfred Schutz. He explain of the human measure will be from a social relation when the human others give a meaning about the form they are done. The research used of a metodology which is kualitative has type descriptive. The result of research in the field show that the society perception about ayam bulek in mariage, ayam bulek is identity for manâs family sides, if the ayam bulek tradition not done by man side, so theÂ manâs family side, will get of bashful to the society. Ayam bulek as an obligation for both of bride. This agreement to do in order to know about total ayam bulek request from manâs family side, so the womanâs family side can make ayam bulek with the same total. Ayam bulek is one of creativity from the manâs family side, because the total of ayam bulek will give of attention by society.